The social security for female workers in Indonesia: A gender equality perspective - Hanoum, Fatma Khalida; Imelda, Johanna Debora (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The number of women workers in Indonesia has increased steadily from 2020 to 2024. Women have reproductive roles and are entitled to rights in the workplace, including maternity leave, miscarriage leave, menstrual leave, and breastfeeding breaks. However, these rights are sometimes not provided according to Indonesian Law Number 13 of 2003 on Manpower. Maternity rights are crucial for women’s well-being and should be granted in line with applicable laws. Methods: The research method used in this journal is a literature review in the form of case studies. Seven case journals in Indonesia were used as the primary references for this study. The research was conducted without comparing the main reference journals. Findings: The study found that women workers, both formal and informal, are employed across various sectors in Indonesia. Social protection guarantees for women, such as social insurance and employer obligations, exist but are not consistently implemented. Some companies cooperate with BPJS Employment, while others provide maternity, miscarriage, menstrual leave, and breastfeeding breaks. However, the lack of proper supervision by the government and labor unions has led to insufficient implementation of these protections, hindering the improvement of women’s welfare. Conclusion: Social protection for women workers must be fulfilled by employers to ensure that women workers can still exercise their reproductive rights. Providing social protection in accordance with applicable regulations for women workers can enhance the social welfare of women workers. Novelty/Originality of this Study: This study offers a unique perspective on the challenges in implementing social protection for women workers in Indonesia, highlighting gaps in supervision and enforcement, as well as the importance of fulfilling reproductive rights to improve women’s well-being.